P05.45 Hydroxyurea (HU) or VAC (vincristine, adriamycin and cyclophosphamide) in a group of recurrent meningioma patients. (19th September 2018) - Silvani, A; Simonetti, G; Elena Antonia, L; Pollo, B; Fariselli, L; Gaviani, P
Abstract: Background: A subset of meningiomas recur after surgery and radiation therapy, no proven effective medical therapy for this sub group of meningioma patients exists. Both recurrent or progressive cases, may exhibit tumor growth involving critical neurovascular structures or diffuse growth, resulting in limited efficacy and higher risk of treatments. Material and Methods: We retrospectively analysed the efficacy and tolerability of systemic chemotherapy with Hydroxyurea (HU) or more complex VAC (Vincristine, Adriamycin and Cyclophosphamide) in a group of recurrent meningioma patients treated at Fondazione IRCCSS Istituto Neurologico Carlo Besta between 2015 and 2017. Results: Twelve patients with high-grade meningioma (8 atypical and 4 anaplastic) were treated with VAC (7) chemotherapy or HU (5). All, patients were heavily pre-treated (median number of 4 recurrences, range 2–7). Responses were assessed using modified Macdonald criteria. The Kaplan-Meier technique was used to estimate PFS and OS. The 95% confidence intervals (CIs) were calculated for all point estimates. The majority of patients came off treatment because of progressive disease. PFS6 rate was 42%. Median PFS was 5.3 months (95% CI: 2.1–9.3 mo), and median overall survival was 19 months (95% CI: 16.5–38.4 mo). No treatment related death occurred. Main treatment-related toxicities were observe in the patients treated by VAC Conclusion: HU and VAC chemotherapies are feasible but these treatments have limited activity in recurrent meningiomas. The optimal systemic therapy for meningioma failing surgery and radiation has yet to be identified due to the small number of prospective clinical trials available